ผลการจัดโปรแกรมกลุ่มสัมพันธ์กีฬาวอลเลย์บอลที่มีต่อทักษะการทำงานเป็นทีมและทักษะกีฬาวอลเลย์บอลของนักเรียนวิทยาลัยอาชีวศึกษา - พงษ์พิณิจ พรหมเนตร (จุฬาลงกรณ์มหาวิทยาลัย, 2020)
The purpose of this research was to (1) study and compare the mean score of teamwork skills and volleyball skill both before and after the treatment of students in the experimental group and (2) compare the mean score of teamwork skills and volleyball skills after the program implementation between students in the experimental group and the control group. The participants were 50 students in 1st year of vocational certificate programs, using volunteer sampling and matching group technique. The participants were divided into 2 groups: an experimental group and a control group, 25 participants each. The experimental group received volleyball group dynamic program whereas the control group did not receive a program. The treatment lasted 8weeks. The research instruments were comprised of a volleyball group dynamic program (IOC = 0.60–1.00), teamwork skills test (IOC = 0.95) and volleyball skills assessment rubric with evaluation form (IOC = 1.00). The results were as follows: (1) After program implementation, the mean score of teamwork skills and volleyball skills of students in the experimental group were higher than those before the implementation at significance level of .05. (2)  After program implementation, the mean score of teamwork skills and volleyball skills of students in the experimental group were higher than students in the control group at significance level of .05.